Malaysia - Venezuela: an anthology of short stories. - Anwar Ridhwan; Aminah Mokhtar; Muhammad Lutfi Ishak; Gabriel Jiménez Emán; Laura Antillano; Wilfredo Machado (Institut Terjemahan & Buku Malaysia Berhad, 2016)
The Malaysia-Venezuela: An Anthology of Short Stories has been published with the aim of establishing ties between two post-colonial countries towards universal understanding and brotherhood.